Product Innovation Of Beetroot (Beta Vulgaris L.) and Dragon Fruit (Hylocereus Polyrhizus) Peel Extract Instant Powder as Antioxidant Potential - Anarisa Budiati; Elvi Sahri Maulinda; Devi Auliya; Ilham Maulana; Muhamad Rafli Razali (Indonesian Journal of Administrative and Clinical Pharmacy, 2026)
Dragon fruit is a type of fruit consumed either in juice drinks or whole. Dragon fruit contains natural antioxidants. Beetroot also has a high antioxidant content. Consuming dragon fruit leaves behind the skin, which becomes waste. The purpose of this research was to optimize the utilization of dragon fruit (Hylocereus polyrhizus) skin waste and to formulate an instant powder preparation combined with beetroot (Beta vulgaris L.) to maintain immunity. The research method included extracting dragon fruit skin with 70% ethanol and drying the beetroot, followed by phytochemical screening evaluation. The thick dragon fruit skin extract was dried using a spray dryer and formulated with beetroot powder to create an instant drink powder. The evaluation results obtained from the dragon fruit skin and beetroot extracts contained flavonoids, saponins, and tannins. The instant powder was red in color, had a distinctive beetroot odor, a water content of 8%, a pH of 6.67, a low-flowing property, and an IC50 of 109.90±5.16. From the results of the hedonic test, 40% of respondents liked instant drink powder.